Response of stiffness and viscosity on the energy ratios at piezo-visco-thermo-elastic medium - Kumar, Sandeep; Kumari, Neelam; Gupta, Vipin; Barak, M.S. (Zielona Góra: Uniwersytet Zielonogórski)
This article presents a mathematical framework that characterizes a transversely isotropic piezo-visco-thermo- elastic medium within the context of the dual-phase lags heat transfer law (PVID) applied to an elastic medium (ES). Specifically, the study investigates the propagation of plane waves within the elastic medium and their interaction with the imperfect interface of the ES/PVID media.
Keywords: dual-phase lag; energy ratios; imperfect interfaces; piezo-thermoelastic; viscosity